Practises to identify and prevent adverse aircraft-and-rotorcraft-pilot couplings—A ground simulator perspective. (August 2015) - Pavel, Marilena D.; Jump, Michael; Masarati, Pierangelo; Zaichik, Larisa; Dang-Vu, Binh; Smaili, Hafid; Quaranta, Giuseppe; Stroosma, Olaf; Yilmaz, Deniz; Johnes, Michael; Gennaretti, Massimmo; Ionita, Achim
Abstract: The aviation community relies heavily on flight simulators as a fundamental tool for research, pilot training and development of any new aircraft design. The goal of the present paper is to provide a review on how effective ground simulation is as an assessment tool for unmasking adverse Aircraft-and-Rotorcraft Pilot Couplings (APC/RPC). Although it is generally believed that simulators are not reliable in revealing the existence of A/RPC tendencies, the paper demonstrates that a proper selection of high-gain tasks combined with appropriate motion and visual cueing can reveal negative features of a particular aircraft that may lead to A/RPC. The paper discusses new methods for real-time A/RPC detection that can be used as a tool for unmasking adverse A/RPC. Although flight simulators will not achieve the level of reality of in-flight testing, exposing A/RPC tendencies in the simulator may be the only convenient safe place to evaluate the wide range of conditions that could produce hazardous A/RPC events.